The identification of the risk factors for cesarean sections in pregnant women - dos Santos Silveira, Lara; Kolling Konopka , Cristine; Flores Jacobi, Luciane (Disciplinarum Scientia | Saúde, 2024)
This study aimed to understand the results of cesarean sections performed in a Teaching Hospital that receives most high-complexity cases, to identify the risk factors related to the choice of this type of childbirth. Binary logistic regression models were built to estimate the odds ratio, with the support of SPSS software. We analyzed 4726 medical records of pregnant women from 2017 to 2018, and 2020 to 2021, with a prevalence of 51.0% and 57.4%, respectively, of cesarean sections. The multiple models found that women over 35 years who have had previous cesarean deliveries, diabetes, polyhydramnios, oligohydramnios, and twin pregnancies were more likely to have a c-section than women who have had multigestational pregnancies. This comprehension enables a more thorough and informed analysis in decision-making, particularly to guarantee the relevance and necessity of cesarean birth.